A Study on Application of False Trade Description towards Halal Food Products - Faradina Ahmad; M. Z. Hussein; N. F. Roslan; Z. J. Husny; A. Rahim N.S; M. Ramzi (International Journal of Supply Chain Management, 2016)
This paper elaborate the scenario of halal industry, the role of halal certification and halal logo in adding value to the halal product and services. Noedays, it is very common to have complaints on the missued of the halal logo. it appears that the logo is being used, arbitrarily to market the product to incite potential group of customer. The author wish to discuss on the application of the regulation as a protection of halal logo in a reported case. A comparison of a previous and current law will show the elaborative and expansion of the scope of the potential abuse in the current time.It is the aims of the authors to contibute at the end of this journal by illuminating easier application of the current law.